2011
DOI: 10.1111/j.1365-313x.2011.04780.x
|View full text |Cite
|
Sign up to set email alerts
|

FRET‐based genetically encoded sensors allow high‐resolution live cell imaging of Ca2+ dynamics

Abstract: SUMMARYTemporally and spatially defined calcium signatures are integral parts of numerous signalling pathways. Monitoring calcium dynamics with high spatial and temporal resolution is therefore critically important to understand how this ubiquitous second messenger can control diverse cellular responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
278
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(284 citation statements)
references
References 72 publications
(83 reference statements)
4
278
1
1
Order By: Relevance
“…Also distinct from a typical signal peptide, TTS does not serve as a transmemrbane helix, can work in the middle or in the C-terminus of the protein, and would not be cleaved. Such sequences would be a useful tool to target other proteins to the tonoplast in genetic engineering processes [32]. Future work will be required to fully characterize this elusive pathway for protein trafficking in plant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also distinct from a typical signal peptide, TTS does not serve as a transmemrbane helix, can work in the middle or in the C-terminus of the protein, and would not be cleaved. Such sequences would be a useful tool to target other proteins to the tonoplast in genetic engineering processes [32]. Future work will be required to fully characterize this elusive pathway for protein trafficking in plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of YFP-TTS fusions were associated with vacuolar membrane, similar to the N-terminal fusion of CBL2-YFP, suggesting that TTS works regardless of its location in the protein (Supplementary information, Figure S4). Interestingly, we further found that TTS was capable of directing different soluble proteins to the vacuolar membrane [32] (Supplementary information, Figure S5A), but it failed to change the subcellular localization of proteins with multiple transmembrane domains (Supplementary information, Figure S5B). CBL2 and CBL3 proteins both bind Ca 2+ Although deduced amino acid sequence and structural analysis suggest that all CBL proteins including CBL2 and CBL3 contain putative EF-hand motifs that contribute to calcium binding [10,33], experimental evidence for the calcium-binding property of CBL2 and CBL3 is limited.…”
Section: Cbl2 and Cbl3 Exhibit Overlapping But Distinct Expression Pamentioning
confidence: 99%
“…To obtain a specific measure of free Ca 2+ concentration in the mitochondrial matrix in planta, we used the genetically encoded sensor Yellow Cameleon 3.6 (YC3.6; Nagai et al, 2004;Palmer and Tsien, 2006;Krebs et al, 2012), which was recently adapted for dynamic measurement of Ca 2+ dynamics in the mitochondrial matrix of Arabidopsis (Loro et al, 2012;Wagner et al, 2015). Reversible Ca 2+ binding by the sensor induces a conformational change that can be detected by a change in the Förster resonance energy transfer (FRET) efficiency between the two fluorophores that are part of the probe (ECFP and cpVenus) such that the FRET ratio (cpVenus:ECFP) increases with increasing free Ca 2+ concentration, thereby providing a quantitative readout.…”
Section: Generation Of Sensor Lines For In Vivo Measurements Of Matrimentioning
confidence: 99%
“…Such studies trace back historically to 3D reconstructions of fixed images at sequential time points, which were used to understand basic subcellular architecture in plants (Donohoe et al, 2013, Staehelin, 1997. Live imaging of FP lines now permits experimental studies of whole organ growth, interactions among neighboring cells, behavior of individual cytoskeletal elements and the ability to trace movement of proteins between cells (Grossmann et al, 2012, Gutierrez et al, 2009, Krebs et al, 2012, Lindeboom et al, 2013, Mathur et al, 2012, Sampathkumar et al, 2011, Teh et al, 2013. With the advent of microfluidic devices, FP markers can be used as biosensors for hormone induction studies during whole root or shoot growth.…”
Section: Live Cell Imaging Using Fluorescent Protein Markersmentioning
confidence: 99%